Creating and Evaluating Instructional Materials to Foster Purposeful Communication in Filipino Language Learning - Samilo, Pearly Jade E. (Journal of Qualitative Research in Education, 2025)
This study developed and evaluated outcomes-based instructional materials to enhance purposeful communication in the Filipino language course, Malayuning Komunikasyon. Using a Type 1 developmental research design anchored on the ADDIE model, the researcher created an OBE-aligned syllabus and a student module responsive to the needs of both teachers and learners. A mixed-methods approach was employed to determine the materials’ appropriateness and acceptability: questionnaires were used to gather quantitative data, while in-depth interviews with teachers and students provided qualitative insights. Quantitative data were analyzed using means and standard deviations, and qualitative responses were examined through thematic analysis using NVivo 12. Findings from the qualitative phase revealed challenges in teaching and learning the course, such as a lack of instructional materials, difficulty achieving competencies, inconsistent delivery, and the need for clear, structured, and culturally relevant resources. The developed instructional materials addressed these gaps, as shown by the quantitative results, which rated the OBE syllabus (M = 4.70) and student module (M = 4.62) as very highly appropriate, and the overall instructional materials as very highly acceptable (M = 4.81). The study concludes that the developed materials effectively align with outcomes-based education principles and significantly support the teaching and learning of Malayuning Komunikasyon. Their adoption is recommended to improve competency attainment and foster more purposeful and meaningful communication in Filipino.